2020
DOI: 10.1038/s41598-020-70797-2
|View full text |Cite
|
Sign up to set email alerts
|

Diverse species-specific phenotypic consequences of loss of function sorting nexin 14 mutations

Abstract: Mutations in the SNX14 gene cause spinocerebellar ataxia, autosomal recessive 20 (SCAR20) in both humans and dogs. Studies implicating the phenotypic consequences of SNX14 mutations to be consequences of subcellular disruption to autophagy and lipid metabolism have been limited to in vitro investigation of patient-derived dermal fibroblasts, laboratory engineered cell lines and developmental analysis of zebrafish morphants. SNX14 homologues Snz (Drosophila) and Mdm1 (yeast) have also been conducted, demonstrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 43 publications
(91 reference statements)
3
18
0
Order By: Relevance
“…It was observed that total fatty acids from neutral lipids (both saturated and unsaturated) were elevated in snx14 knock-out embryos in comparison with wild type and heterozygous embryos. These results confirm that SNX14 has a conserved role in lipid biogenesis [ 61 ].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…It was observed that total fatty acids from neutral lipids (both saturated and unsaturated) were elevated in snx14 knock-out embryos in comparison with wild type and heterozygous embryos. These results confirm that SNX14 has a conserved role in lipid biogenesis [ 61 ].…”
Section: Resultssupporting
confidence: 82%
“…The discrepancies in these studies could be because Bryant et al [ 61 ] used sub toxic doses of morpholinos. Morpholinos are only considered reliable when a mutant model supports morpholino findings due to the previously observed off target effects of morpholinos [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a dynamic coordinated interaction among the recycling, retrograde, and degradative pathways, which maintains normal cellular functions [ 2 , 3 ]. However, if the SNX-PXA-RGS-PXC subfamily, like all other SNX subfamilies, is dysfunctional and disabled to transport receptor cargoes to their appropriate cellular destinations, there will be the impairment of the above-mentioned pathways, which will negatively affect cellular functions, causing disorders, such as those listed in Table 4 [ 17 , 18 , 19 , 20 , 23 , 27 , 33 , 38 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ].…”
Section: Snx-pxa-rgs-pxc Subfamily In Physiology and Pathophysiolomentioning
confidence: 99%
“…SNX14, localized in the lysosome [ 16 ], functions as a negative regulator of the signaling and trafficking of 5-HT 6 R [ 13 ] and probably other receptor cargoes, as well. SNX14 is also localized at the membrane contact site of ER-lipid droplets in yeast, drosophila, and mammals [ 14 , 42 , 91 , 100 ], indicating important roles of SNX14 in lipid drop biogenesis and trafficking of lipid transfer proteins [ 101 ].…”
Section: Snx-pxa-rgs-pxc Subfamily In Physiology and Pathophysiolomentioning
confidence: 99%